The Royal Master and El villano en su rincón Revisited: More than the Motif of the Reluctance to see the King - Garcia García, Luciano (Miscelánea: A Journal of English and American Studies, 2023)
In 1890, in an article titled “Die Nachhamung spanischer Komödien in England unter der ersten Stuarts”, the German scholar A.L. Stiefel solidly demonstrated the clear textual relationship between James Shirley’s The Opportunity and Tirso de Molina’s El castigo del penseque. In 2003, following an intriguing footnote in that article, which pointed to five more dramatic Spanish sources, I postulated another transtextual relationship concerning Shirley’s The Royal Master and Lope de Vega’s El villano en su rincón. My analysis focused on the specific motif that he named “the reluctance to see the king” in the character of the English fool Bombo and the Spanish farmer Juan Labrador. However, after a review of the two plays, it seems clear that there are more textual relationships than the one disclosed in my previous study. Relying on Gerald Genette’s category of transtextuality, this article widens further the scope of the motif, explores its relationship with the topic of court versus country life, unearths architextual transferences of elements of plot and characters, proposes affinities based on the palatine affiliation of both plays and the similarities in the use of the dramatic method of matchmaking, and, finally, reveals the creative use that the Caroline playwright made of his Spanish source.
Keywords: Lope de Vega; James Shirley; El villano en su rincón; The Royal Master; dramatic genres; transtextuality; palatine subgenre